Breast Cancer in Art Painting - Forma, Ewa; Bernaciak, Magdalena; Bryś, Magdalena (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
Breast cancer is an emotive cancer. It is a disease that affects a visible sexual organ and it is the commonest single cause of death of women between 40 and 60 years of age. Nevertheless, this type of cancer was infrequently depicted in art paintings. In this article the themes from the breast cancer in famous art paintings are discussed.